2004
DOI: 10.1007/s00394-004-0487-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in body weight and body composition among women previously treated for breast cancer consuming a high-vegetable, fruit and fiber, low-fat diet

Abstract: The dietary intervention efforts resulted in significant changes in diet toward an increase in plant foods and a decrease in dietary fat. Changes in weight, WHR, BMI, and body composition were not different over time or by study group assignment. Interventions that promote a plant-based diet without specific energy restriction do not appear to promote changes in body weight or body composition in women who have been diagnosed with breast cancer. To adequately examine the role of energy restriction in reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 33 publications
2
34
1
2
Order By: Relevance
“…Other intervention studies have found an effect of increased fruit intake on total energy intake (23)(24)(25)(26)(27) . These intervention studies are either behavioural intervention studies, addressing several dietary and lifestyle factors among free-living individuals (24)(25)(26) , or clinical trials, implementing strict dietary regulations (23,27) . Common to all these studies is that participants were either overweight or obese and may thus have had a high motivation for weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Other intervention studies have found an effect of increased fruit intake on total energy intake (23)(24)(25)(26)(27) . These intervention studies are either behavioural intervention studies, addressing several dietary and lifestyle factors among free-living individuals (24)(25)(26) , or clinical trials, implementing strict dietary regulations (23,27) . Common to all these studies is that participants were either overweight or obese and may thus have had a high motivation for weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the role of fat in increasing energy density of diets, the long-term effect of energy density in defining unhealthy weight gain is not well established. Women's Healthy Eating & Living Trial and Women's Health Initiative, two very large and longterm randomized, double-blind, placebo-controlled trials (RCTs) of low fat, both showed minimal effects on weight [27,28] . Multiple well-controlled RCTs of equal intensity interventions show greater weight loss on highfat diets [29,30] .…”
Section: Fat Intake and Weight Maintenancementioning
confidence: 99%
“…The comparison group was advised to follow general dietary guidelines to reduce disease risk. Significant changes in diet were the result of the dietary intervention, but changes in weight, waist-hip ratio, BMI and body composition were not different in the 2 groups [33]. Other BC patients treated with an intensive dietician-led nutrition education programme, mainly groupbased, experienced a 1.3-kg reduction in body weight at 4 months vs. no change in control patients.…”
Section: Discussionmentioning
confidence: 96%